BEE HONEY PRODUCTION CONCENTRATION IN ROMANIA IN THE EU-28 AND GLOBAL CONTEXT IN THE PERIOD 2009-2018 - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN; Valentin SERBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed honey production concentration in Romania in the period 2009-2018 using the specific indicators: number of beekeepers, bee hives, honey production and yield per bee hive, and methods like: trend equation, Herfindhal-Hirschman concentration index (HHI), regression models, correlations and determination coefficients to examine the gains in comparison with the period 2007-2016. The results pointed out that both the number of bee colonies and honey production increased in a high measure, only honey yield remained stable (20 kg/year). In 2018, Romania came on important positions in the EU-28 top honey producing countries as follows: 2nd position for 1,689.5 thousand bee hives, 1st position for 30,000 tons honey production, 3rd position for 80 average number of bee hives per apiary, and 18th position for 20 kg honey yield per bee hive. In 2018, the distribution of the bee hives and honey production in the territory was: 18.5% South West Oltenia, 16.2% South East, 14.6% North West, 13.6% South Muntenia, 13.3 % North East, 12% Center, 10.6% West and 1.2% Bucharest-Ilfov. Compared to 2009, honey production increased in 2018 in almost all the micro-regions, except North East, where it remained stable. HHI indices had values below 0.15 reflecting a low concentration. Compared to the period 2007-2016, in the interval 2009-2018, the mean for the number of bee hives and honey production increased, the correlation and determination coefficients recorded higher values for the pair of indicators: honey production and the number of bee hives and for the honey production and yield, while for the average yield and the number of bee hives the values were smaller. Regression equations attested that honey production is about 50% determined by the number of bee hives and in smaller proportion by honey yield. Beekeeping has to continue to develop for assuring the pollination of the agricultural crops, the preservation of biodiversity and environment and for providing healthy products for consumers, jobs and incomes for the rural population. The EU and National Programmes for Apiculture will strengthen this sector keeping pace with the increased competitiveness on the EU honey market.